Comparison of Name-Writing Rubrics: Is There a Gold Standard?. (December 2014) - Puranik, Cynthia S.; Schreiber, Samantha; Estabrook, Erin; O'Donnell, Erin
The purpose of this study was to compare name writing using six different rubrics with the aim of ascertaining whether any were better for evaluating preschoolers' name-writing skills. In addition, we investigated the relation between name writing assessed using these six rubrics and children's emergent and conventional literacy skills. Name-writing data were obtained from 346 preschoolers across four data sets and scored using six rubrics: five detailed rubrics and a simple rubric. Results indicated that the scores from these rubrics were highly correlated. Furthermore, the magnitude of the correlations between name-writing scores and children's literacy skills were similar. Findings suggest that these rubrics provide an equivalent index of children's name-writing skills at a single assessment point.